The Leukemia Inhibitory Factor Receptor Gene Is a Direct Target of RUNX1. Issue 1 (January 2016) - Qadi, Abeer A.; Taberlay, Phillippa C.; Phillips, Jessica L.; Young, Arabella; West, Alison C.; Brettingham‐Moore, Kate H.; Dickinson, Joanne L.; Holloway, Adele F.
ABSTRACT: Activation of cytokine signaling via the leukemia inhibitory factor receptor (LIFR) plays an integral role in hematopoiesis, osteogenesis, and placental development, along with mediating neurotrophic mechanisms. However, the regulatory control of the LIFR gene has remained largely unexplored. Here, we characterize the LIFR gene as a novel target of the RUNX1 transcription factor. The RUNX1 transcription factor is an essential regulator of hematopoiesis and is a frequent target of point mutations and chromosomal alterations in leukemia. RUNX1 regulates hematopoiesis through its control of genes important for hematopoietic cell growth, proliferation, and differentiation, including a number of cytokines and cytokine receptors. LIFR is regulated by two alternate promoters: a placental‐specific and a ubiquitously active general promoter. We show that both of these promoters are regulated by RUNX1. However, in myeloid cells LIFR expression is driven solely by the general LIFR promoter with our data indicating that the placental promoter is epigenetically silenced in these cells. While RUNX1 activates the LIFR general promoter, the oncogenic RUNX1‐ETO fusion protein generated by the t(8;21) translocation commonly associated with acute myeloid leukemia represses promoter activity. The data presented here establish LIFR as a transcriptional target of RUNX1 and suggest that disruption of RUNX1 activity in myeloid cells may result in altered LIFR signaling in these cells. J. Cell. Biochem. 117: 49–58, 2016. © 2015 Wiley Periodicals, Inc.